A descriptive analysis of concomitant opioid and benzodiazepine medication use and associated adverse drug events in United States adults between 2009 and 2018 - Kathryn K. Marwitz; Marwa Noureldin (Elsevier, 2022)
Background: In 2016, the Centers for Disease Control and Prevention (CDC) published guidelines for prescribing opioids for chronic pain in response to the opioid epidemic and recommended avoiding concomitant use of opioid and benzodiazepine medications whenever possible. However, based on a recent report, 16% of overdose deaths involving opioids also involved benzodiazepines. Objective: The objectives of this study were to examine 1) trends in concomitant opioid and benzodiazepine usage and factors associated with utilization 2) and related adverse event reporting before and after the publication of CDC chronic pain prescribing guidelines. Methods: This study employed a retrospective data analysis of the National Health and Nutrition Examination Survey (NHANES) and FDA Adverse Event Reporting System (FAERS) databases between 2009 and 2018. Descriptive statistics and logistic regression were used to examine characteristics and temporal trends in people taking or reporting adverse events with opioid, benzodiazepine, and both medications. Results: Among those taking an opioid medication, 19.7% were also taking a benzodiazepine within the same 30 days. Characteristics for those who reported taking both medications together include being female, non-Hispanic White, being middle aged, and having a lower household income. Concomitant medication use rose between 2009 and 2016 and declined in 2017-2018. Among FAERS reports examined with an opioid suspect medication, 17.9% also included a benzodiazepine suspect medication. Over time, there was an increase in identified FAERS reports involving concomitant opioid and benzodiazepine medications. Conclusions: Concomitant opioid and benzodiazepine use was detected in a small but notable proportion of NHANES survey participants and FAERS reports between 2009 and 2018. Further research examining causal associations between opioids, benzodiazepines, and identified social risk factors are needed to inform prescribing and to best tailor public health interventions to address physical and mental illness safely and effectively across the population.